Implementasi Kewajiban Diversi Bagi Anak Pelaku Tindak Pidana Kekerasan di Kepolisin Sektor Tenayan Raya Berdasarkan UU No. 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak - Andriyan, Dedi (DOKTRINA: JOURNAL OF LAW, 2024)
The purpose of the study was to analyze the implementation of the obligation to divert for children who commit violent crimes, the factors inhibiting its implementation and to find efforts to overcome the obstacles. The research method is a type of sociological legal research, where the location of the research was carried out at the Tenayan Raya Police Sector. The results found that the implementation of the obligation to divert for children who commit violent crimes in the region has not been implemented properly. The inhibiting factors are: regulatory factors, law enforcement/government factors, facilities/facilities factors and community factors. Efforts to overcome obstacles, namely regulatory factors, the police and government agencies need to socialize Law No. 11 of 2012. Law enforcement factors, should increase cross-sector cooperation and coordination. Facilities/facilities factors, the police should provide a special room for assessment. Community factors, officers should take a more humanistic approach; The police should educate the perpetrator's family so that the request for compensation is in accordance with the perpetrator's ability; a certain approach should be taken to the victim/his family so that a diversion agreement is reached; The victim's family should be given an understanding that imprisonment is not for children; the victim's family should ask for compensation according to the victim's medical expenses.